Assessment of the content, usability, and benefits of the WeChat-based programme for dog bite victims in China: A prospective observation study. Issue 50 (11th December 2020) - Du, Zhe; Huang, Wei; Zhang, Yajun; Zhang, Peng; Liu, Zhongdi; Chen, Qingjun; Wang, Chuanlin
Abstract : Abstract: WeChat in China has been used for public health education and the prevention of diseases. This study introduced a WeChat-based program for rabies prevention and evaluated the users' satisfaction with the program using the technology acceptance model. An online satisfaction questionnaire was used to survey 315 users who had followed the WeChat official account in China, and their satisfaction scores were assessed and analyzed. The users were generally satisfied with the WeChat-based program as an educational and instructional tool with the mean satisfaction score for each item ranging from 3.9 to 4.6 out of a maximum of 5.0 and the total mean satisfaction score of 41.5 out of a maximum of 50.0 ( SD  = 4.3). Urban users showed more satisfaction than rural users ( P  = .03). Users who were satisfied also reported that they intended to recommend WeChat to others ( P  = .00). Findings from the present study indicated that WeChat was considered a useful educational and instructional tool for dog-bite victims among young and urban population. This model of a WeChat-based program for rabies prevention should be expanded to other areas in China.